Heroes and their communities: A longitudinal study of four medieval romances - Holmes, Dawn Melanie (My University, 2001)
This dissertation examines the principles that shape heroic behaviour in a selection of medieval texts that were directed towards a lay audience. These popular texts, written in the vernacular, both reflect and affirm the value systems of their intended audiences. I consider the nature of the societies they depict in terms of cohesiveness and stability, and then determine the role of the hero within such a structure. The struggles of the heroes, in turn, reveal the preoccupations and assumptions of their social milieu inside and outside of the text. In looking to romance for historical truths, this study reexamines the ways in which we read these texts. Moreover, my findings contribute to the study of individuality by exploring the ways in which medieval society negotiated the relationship between the desires of the individual and the needs of the community. I begin with an analysis of the Chanson de Roland , long read in light of its contributions to historical research, and, from there, apply the same methodology to four twelfth-century French romances: Partonopeu de Blois , Béroul's Roman de Tristan , Chrétien de Troyes' Lancelot ou le Chevalier de la Charrette , and Robert le Diable . Close readings of these narratives reveal that they all espouse a communal ethic that values honour, loyalty, and harmony. The next part of this dissertation explores fifteenth- and sixteenth-century English adaptations of the romances: Partonope of Blois , Sir Thomas Malory's Book of Sir Tristram de Lyones and the "Knight of the Cart" episode, and Robert the Devyll . The later romances depict a more fragmented society wherein characters are encouraged to pursue their own personal goals within the parameters established by fixed moral codes. By juxtaposing a synchronic study of the early romances with an analysis of their adaptations composed three hundred years later, this project demonstrates the transformation of a culture centered around the protection and promotion of the common good into a more modern ethos that recognizes the autonomy of the individual.
Keywords: English Language and Literature; English Language and Literature